Motubang: A Mobile Application to Monitoring Children Growth and Development Status - Wijaya, Rahmadi; Mandasari, Rizza; Fikry, Mandasari; Jauhar, Fikry; Gandia, Aldhie (International Journal of Engineering and Technology, 2019)
Children’s growth and development is crucial point that must be monitored by each parent to prepare a healthy and resilient generation, especially during the golden period (0 – 3 years). Unfortunately, many parents cannot monitor the child, either because of busy or lack of awareness. Based on Indonesia Ministry of Health, 1.1 Million of Indonesian child under five years, experienced growth and development disorder, and many of it caused by late of identification. In this paper, we propose Motubang - a mobile application for monitoring children’s growth and development. With this mobile application, problems and developmental disorders can be detected at an early stage so that appropriate interventions can be done. This research involve parent who have children aged 0 – 6 years, and medical team in Puskesmas Cibiru Hilir. Motubang is the tools project for Cross-Sectional Study to find correlation of nutritional status and the development of children in age 0 – 6 years in Puskesmas Cibiru Hilir.